Not who we expected [large type] - Black, Lisa, 1963- (Black, Lisa, 1963- Locard Institute thriller, 2025)
"Now forensic experts, Ellie Carr and Rachael Davies are pulled into solving a deadly mystery unfolding in the shadow of a celebrated rock star. The two are enlisted by legendary rock star Billy Diamond to find his missing daughter. A level-headed student at Yale, Devon left six months earlier with her boyfriend, Carlos, for a career development retreat in Nevada. Her calls and notes became less frequent until they stopped. Billy wanted to give his daughter space -- but after learning Carlos' body was found a few miles upstream from the ranch, he needs answers. Rachael and Ellie hatch a plan -- as Ellie goes undercover, Rachael will work with Billy to find out about Devon. But Rachael has a second agenda, to find out why Billy seems so familiar with her late sister Isis, whose little boy Rachael is raising. The music idol is hiding something, but what? The southwest ranch is full of surprises. Devon is not only alive but thriving, and no one mentions Carlos. The attendees follow their leader, Galen, with slavish devotion, and their daily mind-body exercises stretch from brain-numbing to downright treacherous. If Galen is behind some nefarious scheme, how does it relate to the rock star and his daughter?"--